The "spaghetti bowl" of IIAs: The end of history? - Joachim Karl (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2014)
The universe of international investment agreements continues to grow, albeit at a slow pace and with a focus on regional agreements. This may further reduce the prospects for multilateral investment rulemaking and perpetuate the existing structure of the IIA regime.
Keywords: 330